2018
DOI: 10.3390/ijgi7010026
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Accelerating Dissolved Vector Buffer Generation in Distributed In-Memory Cluster Architecture

Abstract: Abstract:The buffer generation algorithm is a fundamental function in GIS, identifying areas of a given distance surrounding geographic features. Past research largely focused on buffer generation algorithms generated in a stand-alone environment. Moreover, dissolved buffer generation is dataand computing-intensive. In this scenario, the improvement in the stand-alone environment is limited when considering large-scale mass vector data. Nevertheless, recent parallel dissolved vector buffer algorithms suffer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The value of the burned area was obtained from the buffer analysis in ArcGIS. The algorithmic formula used for buffer creation was expressed as Fbuffer (D, r) (Shen et al, 2018) showed in Equation 1.…”
Section: Estimation Of Burned Areamentioning
confidence: 99%
“…The value of the burned area was obtained from the buffer analysis in ArcGIS. The algorithmic formula used for buffer creation was expressed as Fbuffer (D, r) (Shen et al, 2018) showed in Equation 1.…”
Section: Estimation Of Burned Areamentioning
confidence: 99%
“…In our previous work, we proposed a parallel vector buffer generation method, the Hilbert Curve Partition Buffer Method (HPBM) [8], that takes advantage of the in-memory architecture of Spark [18]. HPBM is based on the Hilbert filling curve to aggregate adjacent objects and thus to optimize the data distribution among all distributed data blocks and to reduce the cost of swapping data among different blocks during parallel processing.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, the performance is limited when processing large-scale spatial data. Developments in parallel computing technologies provide a prerequisite for high-performance buffer generation, and several parallel strategies have been proposed to solve the bottlenecks [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their large storage space occupancy, raster-based methods are generally not applied to large-scale spatial data, and the related research mainly focuses on the calculation of raster buffers using a serial computing model [5,6]. For vector-based methods, the edge constraint triangulation method [7] and the buffer equation approximation strategy are widely used [8] in buffer generation; in addition, in order to deal with large-scale data, several parallel strategies have been proposed to solve the vector-based buffer and overlay generation problems [9][10][11][12][13][14][15][16][17]. However, the performance is still far from satisfactory as it is impossible to support real-time buffer-overlay analysis using the traditional methods, even when high-performance computing technologies are applied.…”
Section: Introductionmentioning
confidence: 99%
“…However, the performance is still far from satisfactory as it is impossible to support real-time buffer-overlay analysis using the traditional methods, even when high-performance computing technologies are applied. For example, Shen [10] proposed a parallel vector buffer generation method, HPBM, based on Spark [18], and conducted an experiment on a high-performance cluster which compared HBPM to three optimized parallel methods and the popular GIS software programs ( Table 2); as shown in the table, HBPM outperformed the other traditional data-oriented methods and is able to generate buffers for 597k linestring objects in around 3 min. As another example, Puri [16] presented a parallel GIS system, MPI-GIS, for polygon overlay processing of two GIS layers which employs R-tree for efficient indexing and identification of potentially intersecting sets of polygon objects; using MPI-GIS, the processing time of hundred-thousand-scale datasets is in the ten-second-level.…”
Section: Introductionmentioning
confidence: 99%